Perang Salib (Penyebab Pecahnya Perang Salib, Apa Manfaat yang Diperoleh Umat Islam dan Nasrani dari Perang Salib) - Sri Nilawati; Hasaruddin; Syamzan Syukur (Jurnal Ilmu Pendidikan dan Sosial, 2024)
The Crusades occurred because a number of Christian cities and holy places were occupied by Islam since 632 AD. The Christian military used the cross as a symbol to show that this war was holy and aimed at liberating the holy city of Baitul Maqdis (Jerusalem) from Muslims/to show that the war was right. If it is true that it is a holy war, then all Western fleets and troops leaving for the battlefield are obliged to wear the cross attribute, whether worn on the sails of their boats, on their flags, starting from team flags and troop flags, shields, armor and various other equipment. The research method used is a qualitative method with a literature study type of research. Primary data sources use supporting references and secondary data sources use several journals and books. Analysis of the data used uses content analysis. The results of this research found that the crusades were the result of the birth of expansionism in Europe as in the efforts of the Seljuq against the Byzantine Empire. In the expansion movement carried out by Alp Arselan was the Manzikart event, in 464 AH, Alp Arselan's army with a strength of 15,000 soldiers, defeated the army Romans numbering 200,000 people. This event planted the seeds of hostility and hatred among Christians towards Muslims. This hatred increased after the Seljuq Dynasty seized Baitul Maqdis in 471 AH from the power of the Fatimid Dynasty based in Egypt. The Seljuq rulers set regulations for Christians who wanted to make a pilgrimage there. They felt that this regulation was very difficult for them. To obtain the freedom to make a pilgrimage to the holy Christian land, Pope Urban called on Christians in Europe to carry out a holy war.